Psychological Impact of the COVID-19 Pandemic on Children and Adolescents With and Without Mental Disorders - Susanne Gilsbach; Beate Herpertz-Dahlmann; Kerstin Konrad; Kerstin Konrad (Frontiers Media S.A., 2021)
Background: The previous and current studies highlight the psychological distress caused by coronavirus disease 2019 (COVID-19)-associated restrictions among the general population, especially among children and adolescents; however, few studies have examined children and adolescents with a mental disorder. The current study aimed to explore whether youth with mental disorders show a higher pandemic-associated psychological burden than healthy children and adolescents and to determine which psychiatric diagnoses are particularly associated with a higher distress level.Methods: In this study, 144 children and adolescents between the ages of 6 and 18 years with a mental disorder and 48 children and adolescents within the same age range without a mental disorder, and their caregivers, completed questionnaires assessing the pandemic-associated trauma symptoms (the Child Report of Post-Traumatic Symptoms [CROPS] and the Parents Report of Post-Traumatic Symptoms [PROPS]). Additionally, we asked specific questions about the pandemic-associated stress factors, such as financial problems, prolonged screen times, or loneliness.Results: Children and adolescents with a mental illness showed a significantly higher psychological burden than their mentally healthy peers. Female gender was a risk factor for a higher self-reported psychological burden, and younger age was associated with a more extensive parent-reported psychological burden. The patients with a depressive disorder showed significantly higher levels of psychological distress associated with the COVID-19 pandemic than the patients with an attention deficit and/or a conduct disorder.Conclusions: Children and adolescents with a mental illness, particularly, female children and individuals with a depressive disorder, are at an increased risk of suffering from pandemic-associated psychological distress. Adequate mental health care options, such as telepsychiatry, are indispensable.